Dopamine receptor D2 and ankyrin repeat domain containing one in temporomandibular disorder of adolescents - Franco, Gizele Batista; Faturri, Aluhe Lopes; Meger, Michelle Nascimento; Paiva Bertoli, Fernanda Mara; Wambier, Letícia Maira; Scariot, Rafaela; Souza, Juliana Feltrin; Küchler, Erika Calvano; Brancher, João Armando (International journal of paediatric dentistry, 2019)
Background Temporomandibular disorder (TMD) is a multifactorial condition that combines environmental and genetic factors and its prevalence increases during adolescence. Aim To investigate the association between TMD and genetic polymorphisms in the DRD2 and ANKK1 in a population of Brazilian adolescents. Design The TMD group included adolescents diagnosed with any of the following TMD subgroups according to the RDC/TMD criteria: myofascial pain, arthralgia and disc displacement and painful TMD. Genomic DNA for molecular analysis was extracted from buccal cells, and genetic polymorphism rs6275 in DRD2 and rs1800497 in ANKK1 were genotyped by real‐time polymerase chain reactions using the TaqMan assay. Data were analysed using the Epi Info 3.5.7 and Stata software, with significance level of 0.05. Results Two hundred fifty‐one individuals were included in this study, 148 subjects presented TMD. For disc displacement, the genetic polymorphisms rs6275 was associated in a recessive model (P = 0.04), whereas the rs6276 and rs1800497 presented only a borderline association in a recessive and dominant models, respectively (P = 0.07 and P = 0.06). Conclusion The genetic polymorphism rs6275 in DRD2 was associated with disc displacement in Brazilian adolescents.